THE IMPACT OF PSYCHOLOGICAL FACTORS IN DECISION-MAKING TO START AND DEVELOP ENTREPRENEURIAL INITIATIVES - Yani, Ahmad (PT. LITERASI SAINS NUSANTARA, 2024)
There is a global increase in interest in entrepreneurship among individuals from diverse backgrounds. This phenomenon is fuelled by various factors, including economic, technological, and cultural changes. However, psychological factors also have a significant influence in shaping entrepreneurial intention and behaviour. This research aims to examine the impact of psychological factors in decision-making to start and develop entrepreneurial initiatives. The research method is a qualitative literature review that takes data from Google Scholar for the period 2006 to 2023. The study results show that the impact of psychological factors in decision-making to start and develop entrepreneurial initiatives is significant. Individual motivation, risk perception, tolerance for uncertainty, self-confidence, ability to manage stress, and social support are some of the key psychological factors that influence the entrepreneurial decision-making process. Understanding the complex interactions between these factors is key to developing a better understanding of entrepreneurial motivation and behaviour.